Parliamentary Election Cycles and the Turkish Banking Sector - Christopher Baum; Mustafa Caglayan; Oleksandr Talavera (Turkish Economic Association, 2009)
This paper analyzes the effects of parliamentary election cycles on the Turkish banking system. Using annual bank-level data representing all banks in Turkey during 19632005, we present evidence of meaningful differences in the structure of bank assets, liabilities and financial performance across different stages of the parliamentary election cycle. However, we find that government-owned banks behavior does not differ from either domestic or foreign-owned private sector banks before, during or after elections. Our estimates also show that government-owned banks underperform their domestic and foreign-owned private sector counterparts.
Keywords: G21; G28; 330; Elections; state banks; domestic banks; foreign-owned banks; loans; interest rate margin; Wahl; Bank; Öffentliches Unternehmen; Bilanzstrukturmanagement; Türkei